Preparation, characterization and encapsulation of diorganotin complexes as potential anticancer drugs / Siti Nadiah Mohd Rosely - Siti Nadiah , Mohd Rosely (2018)
A series of diorganotin(IV) complexes with Schiff base ligands derived from 3-hydroxy-2-naphthoic hydrazide (NAH) and tris(hydroxymethyl)aminomethane (TRIS), were synthesized and characterized using infrared (IR), 1H and 13C nuclear magnetic resonance (NMR) spectroscopies and elemental analyses. Besides, the crystal structure of one of the complexes was determined by single crystal X-ray diffraction (SCXRD). The in vitro cytotoxic activities of the Schiff base ligands and their diorganotin(IV) complexes were evaluated against two human carcinoma cell lines, namely human colon carcinoma cell line (HT29) and hormone-dependent breast carcinoma cell line (MCF7). Among the synthesized complexes, [N’-(4-decyloxy-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato]dimethyltin(IV) (NA1) and (2-{[1,1-bis(hydroxymethyl)-2-oxidoethyl]iminomethyl}-4-dodecyloxy-2-oxidobenzylidene)dibutyltin(IV) (TB2) were the most active. The percentage of encapsulation efficiency and percentage of drug loading for niosome-encapsulated for seven diorganotin(IV) complexes were investigated. While only one niosomes-complex system was chosen as an exemplary detailed characterization, covering encapsulation efficiency and drug loading, size distribution, zeta potential and morphology of the carriers as well as an in vitro release study was performed. Niosomes with the mean diameter approximately 100 nm in size with low polydispersity index of 0.3 was prepared through ethanolic injection method. Niosome-loaded with ND2 complex exhibited high encapsulation efficiency in the range of between 80 - 99%. The results from a zeta potential measurement showed that the formulation is relatively stable with the value in a range of -25 to -36 mV. The drug release rate was slow, about 20% cumulative in three months.